Investigation of The Relationship Between the Tactical Skills Used by Football Players and Their Maximum Performance Levels - Kemal Göral; Serdar Yıldırım (Türk Spor ve Egzersiz Dergisi)
This study was conducted to investigate the relationship between the tactical skills used by amateur and professional league football players and their excellent performance levels. A total of 906 licensed football players, including 671 male and 235 female athletes, who play at amateur and professional levels in football leagues, participated in the research. Three different forms were used as data collection tools: Personal Information Form, Tactical Skills in Sports and Excellent Performance in Sports Scale. According to the findings of the study, 25.9 of the football players participating in the study were female and 74.1% were male. While the mean age of female football players was 20.06±3.18, the average age of male football players was determined as 23.34±5.62. In the study, a significant difference was found between the sub-dimensions of tactical skills in sports and the total scores of male and female football players. Similarly, it has been observed that male athletes have higher scores than female athletes in excellent performance scores. According to the years of playing licensed football, there were significant differences in all sub-dimensions of the tactical skills of the football players, between the athletes who played football between 1-5 years and all other groups who played football for more years (p